2005
DOI: 10.1158/1535-7163.mct-04-0241
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of RAD21 gene expression decreases cell growth and enhances cytotoxicity of etoposide and bleomycin in human breast cancer cells

Abstract: A genome-wide case-control association study done in our laboratory has identified a single nucleotide polymorphism located in RAD21 as being significantly associated with breast cancer susceptibility. RAD21 is believed to function in sister chromatid alignment as part of the cohesin complex and also in double-strand break (DSB) repair. Following our initial finding, expression studies revealed a 1.25- to 2.5-fold increased expression of this gene in several human breast cancer cell lines as compared with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…The protein interaction network of Rad21 and its coexpressed genes was mapped (Figure ). KEGG pathway analysis (Figure ) showed that Rad21 was associated with the cell cycle and RNA transport . CRM1/chromosome region stabilizing protein (XPO1, export protein 1) is involved in RNA transport under the action of RNA polymerase, whose function is highly related to Rad21 protein expression (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…The protein interaction network of Rad21 and its coexpressed genes was mapped (Figure ). KEGG pathway analysis (Figure ) showed that Rad21 was associated with the cell cycle and RNA transport . CRM1/chromosome region stabilizing protein (XPO1, export protein 1) is involved in RNA transport under the action of RNA polymerase, whose function is highly related to Rad21 protein expression (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, all seven AGs were related to the cell cycle. Classical cell cycle–specific agents such as etoposide, irinotecan, and bleomycin have been used prevalently in various cancers (Atienza et al, 2005 ), and many novel drugs such as palbociclib and CFI-402257 are also related to the cell cycle (Thu et al, 2018 ). As a member of CDKs, CDK1 plays a crucial role in the cell cycle process (Xiao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, artificially diminishing the expression of the RAD21 gene (RADiation sensitive 21), which encodes for one of the cohesin components, was reported to enhance the cytotoxicity of the DNA damaging agents etoposide and bleomycin in cancer cells. 10 A similar effect would be expected by HDAC inhibitors that affect SCR through cohesion impairment. Moreover, it is worthy of note that the genetic instability caused by HDAC inhibition might also contribute to the development of new tumoral processes or chemoresistance by promoting the acquisition of extra mutations.…”
mentioning
confidence: 72%